A comparative study of the area of the canal space obturated by thermoplasticized gutta-percha techniques - (:unkn) unknown (My University, 1994)
Two thermoplasticized gutta-percha techniques were evaluated for the percentage area of canal obturated by gutta-percha and compared with the lateral condensation of gutta-percha technique. All obturation systems were used in conjunction with Grossman's sealer. Single rooted teeth were obturated by either injected thermoplasticized gutta-percha (Ultrafil), thermoplasticized gutta-percha with metal carrier (Thermafil) or lateral condensation of gutta-percha. There were ten specimens in each group. The teeth were embedded in resin, sectioned at 1.5 mm, 3 mm and 4.5 mm from the root apex and examined with a stereomicroscope. Specimens filled by Ultrafil and Thermafil contained a significantly higher percentage of gutta-percha than specimens filled by the lateral condensation technique at every level. However no difference was found between Ultrafil and Thermafil. Three lateral condensation specimens showed voids at the 1.5 mm section; no voids were detected in specimens filled by Ultrafil or Thermafil at any level.
Keywords: Humans; Histological Techniques; Dental Pulp Cavity; Root Canal Obturation; Gutta-Percha; In Vitro Techniques; Evaluation Studies as Topic